Current status of transcatheter mitral valve replacement: systematic review and meta-analysis - Alperi, Alberto; Avanzas, Pablo; Leon, Victor; Silva, Iria; Hernández-Vaquero, Daniel; Almendárez, Marcel; Álvarez, Rut; Fernández, Félix; Moris, Cesar; Pascual, Isaac (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Mitral Regurgitation (MR) has a strong impact on quality of life and on mid-term survival. Transcatheter mitral valve replacement (TMVR) is rapidly expanding and a growing number of studies have been published recently. Methods: a comprehensive systematic review of published literature providing clinical data on TMVR for patients with significant MR was performed. Early- and mid-term clinical and echocardiographic outcomes were evaluated. Overall weighted means and rates were calculated. Risk ratios or mean differences were obtained when comparing pre- and post-procedural data. Results: a total of 12 studies (all observational or single-arm trials) and 347 patients who underwent TMVR with devices clinically available or under clinical evaluation were included. Thirty-day mortality, stroke and major bleeding rates were 8.4%, 2.6%, and 15.6%, respectively. Pooled random-effects resulted in a significant reduction of ≥grade 3+ MR (RR: 0.05; 95%CI: 0.02 – 0.11; p<0.001) and in the rates of patients in NYHA class 3-4 after the intervention (RR: 0.27; 95%CI: 0.22 – 0.34; p<0.001). Additionally, the pooled fixed-effect mean difference for quality of life based on the KCCQ score yielded an improvement in 12.9 points (95%CI:7.4-18.4, p<0.001), and exercise capacity improved by a pooled fixed-effect mean difference of 56.8 meters in the 6-minute walk test (95%CI 32.2-81.3, p<0.001). Conclusions: Among 12 studies and 347 patients comprising the updated evidence with current TMVR systems there was a statistically significant reduction in ≥grade 3+ MR and in the number of patients exhibiting poor functional class (NYHA 3 or 4) after the intervention. Overall rate of major bleeding was the main shortcoming of this technique.